An implicit research methodology to evaluate advertising effectiveness in Esports streaming based on viewers’ gaze, cognitive and emotional responses. - Frano Giakoni; María López; Francisco Segado; Aarón Manzanares; Javier Mínguez (Sport TK, 2022)
It is difficult to assess the real effectiveness of the sponsorship of esports for a brand. An initial approach would be to calculate the visibility of the brands’ ads during a broadcast, which is usually characterized in terms of exposition time. Classically, this time was computed manually by visual inspection, but computer vision algorithms have recently automated this process, providing some sort of cost effectiveness parameter. This study goes a step further by proposing a new and complementary research methodology to assess the effectiveness of ads in esports, based on implicit research techniques such as electroencephalogram, galvanic skin response, eye-tracking, and analysis of the gaze behavior of the viewers, along with their emotional and cognitive states. Although there is no scarcity of studies on market investigation and advertising employing these research methodologies, these have not been applied to esports research yet. This study reports the implementation of this methodology in a case study with 48 participants during a given esports match. It is also demonstrated how these new metrics, which capture the non-conscious states of viewers, can be used to assess the performance of ads (in this case, brand logos). Additionally, it is shown how ad exposition time (widely accepted metric to assess ad effectiveness) presents an error of 60.18% with respect to real visualization, and how the methodology presented herein can be used to find the best placements for ad/brand exposure during esports broadcast.